Our students do learn mechanical and electrical engineering / Chan Hun Beng … [et al.] - Chan, Hun Beng; Raja Mohd Noor, Raja Nor Husna; Ainun Musir, Adhilla; Keria, Roziah; Kamarudin, Faizah; Zakariah, Zulfairul (Unit Penerbitan PKAPP, 2024)
It is common that a civil engineering graduate always act as a Superintending Officer of infrastructure projects; and sometimes even if the projects were buildings dominated. Well, if you are a project manager, you are expected to know about almost everything if not their details of all. Jack of all trades! Thus, our students were exposed to mechanical and electrical engineering practices.